Management strategies to improve reproductive performance of Brahman cross cattle (Bos indicus) in East Java, Indonesia - Dian Ratnawati; D. A. Indrakusuma; Lukman Affandhy; F. Cowley; D. Mayberry; D. Poppi (Jurnal Ilmu Ternak dan Veteriner, 2016)
The demand for meat in Indonesia cannot be supplied by domestic cattle production, and so breeder cattle stock are imported from abroad overseas to increase domestic production. A commonly imported breed is Brahman cross bred (Bx). Smallholder farmers have reported a wide range of problems associated with Bx cow reproductive performance. The purpose of this study was to identify changes in the reproductive performance of Bx cows by providing advice to farmers on improved management strategies, such as: maintaining body condition score (BCS) of cow> 3, appropriate estrous detection and weaning at 5- 6 months. This study was conducted from October 2011 – December 2013 by using 189 Bx cows and 151 farmers. The research was conducted in two sub districts of Lamongan district (East Java), Modo and Sambeng. Cattle were fed diets based on crop residues and were supplemented with green feeds, by-products (rice bran) and concentrate during the last 2 months of pregnancy and early lactation. The reproductive performance of cows improved during the study, there were a shorter lactation length/early weaning (reduced from 188 days to 153 days) and improved BCS (from 3.0 to 3.3). The length of postpartum anestrous interval (PPAI) decreased from 198 days to 98 days. Cycling to conception decreased from 75 days to 64 days and days open decreased from 217 days to 118 days over the length of the study. This was associated with improvement in BCS of cows at calving (from 3.0 to 3.3) and a shorter lactation length (reduced from 188 days to 153 days). There was no change in the average birth weight of calves (31.8 kg). There was no change in average weaning weight of calves over the year and average daily gain of calves while suckling 0.7 kg/day. The pre weaning calf mortality rate was decreased during this study (from 13% to 6%). This project demonstrated that Brahman cross cows can successfully be kept by smallholder farmers in Indonesia if appropiate management is used. It can be concluded that improving management, such as maintaining body condition score of cow >3, estrous detection, appropiate mating and weaning at 5-6 months can improve reproduction performance of Brahman cross.